Peran Transparansi Keuangan dalam Memediasi Pengaruh Penyajian Kas terhadap Kualitas Laporan Keuangan pada Usaha Mikro di Kalianak Morokrembangan - Aliatus Nurrochmah; Anggelina Wijaya Tan; Sri Rahayuningsih (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the role of financial transparency in mediating the effect of cash presentation on the quality of financial statements in micro businesses in Kalianak Morokrembangan, Surabaya. The approach used is descriptive qualitative through in-depth interviews with three smoked fish business actors as representatives of the traditional food trade sector. The results show that systematic cash presentation has a positive effect on financial statement quality, but this effect is stronger when mediated by a high level of financial transparency. Transparency has been proven to increase the reliability, relevance, and comprehensibility of financial statements through information disclosure and the availability of transaction evidence. Business actors who routinely record transactions and disclose their financial statements to family or business partners show a significant increase in credibility and cash flow stability. This study confirms that the integration of cash recording and transparency is an important foundation in building a simple and accountable accounting system for micro businesses.